2015
DOI: 10.1371/journal.pone.0143129
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus Load Is High despite Preserved Interferon-β Response in Cystic Fibrosis Bronchial Epithelial Cells

Abstract: Lung disease in cystic fibrosis (CF) is often exacerbated following acute upper respiratory tract infections caused by the human rhinovirus (HRV). Pathophysiology of these exacerbations is presently unclear and may involve deficient innate antiviral or exaggerated inflammatory responses in CF airway epithelial cells. Furthermore, responses of CF cells to HRV may be adversely affected by pre-exposure to virulence factors of Pseudomonas (P.) aeruginosa, the microorganism that frequently colonizes CF airways. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…The lack of apoptosis in CF AEC supports previous work in our laboratory where dampened apoptosis was observed following RV infection (8). This study supports data suggesting RV infection drives lytic cell death (7), potentially responsible for the increased viral load observed in CF (8,22).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lack of apoptosis in CF AEC supports previous work in our laboratory where dampened apoptosis was observed following RV infection (8). This study supports data suggesting RV infection drives lytic cell death (7), potentially responsible for the increased viral load observed in CF (8,22).…”
Section: Discussionsupporting
confidence: 90%
“…Cleavage of the phosphatidylserine receptor by neutrophil elastase specifically disrupts phagocytosis of apoptotic cells (26,27) and as free neutrophil elastase is increased in the CF airway (28,29), it may explain the reduced apoptotic response and defective efferocytosis observed in the CF airway. Additionally, as suggested by the data in this study, a delayed apoptotic response following RV infection of AEC may also contribute to the defective apoptosis and increased viral load observed in CF (8,22). The study by Vandivier et al also found evidence of secondary necrosis following delayed apoptosis, potentially further exacerbating inflammation in the airway via release of DAMPs such as IL-1 signaling (26).…”
Section: Discussionsupporting
confidence: 61%
“…These findings indicate that most of the P. aeruginosa strains found in the environment and causing infections in CF patients are able to modulate the antiviral response since most of P. aeruginosa isolates are of group 1 or group 2. Two earlier studies could also demonstrate that P. aeruginosa is able to modulate the antiviral response of epithelial cells (31,32). In addition, the first study could demonstrate a difference in virus-induced IFN expression between healthy and CF-derived cells.…”
Section: Discussionmentioning
confidence: 93%
“…In response to infection with respiratory viruses, studies have also observed increased IL-8 production in CF vs. non-CF pAEC (152,153), which is analogous to in vivo findings in pediatric CF patients with rhinovirus infection (154). However, other studies have reported no difference in inflammatory cytokine production as a result of in vitro viral infection (155,156). The filamentous fungi Aspergillus fumigatus is emerging as an important early life CF pathogen increasingly detected in pediatric CF airways (157,158), with A. fumigatus infection associated with increased air trapping among 5 year old CF patients (159).…”
Section: Primary Airway Epithelial Cellsmentioning
confidence: 59%